Complicaciones del embarazo en adolescentes usuarias del Hospital General Macas. Año 2015 - Torres Torres, Lérida Alexandra (2016)
This study has the purpose to investigate the complications of pregnancy in adolescent users General Hospital Macas, technical survey and observation 40 pregnant adolescents, the research design was descriptive cross, literature and applied field. As a result it was found that adolescents with complications of pregnancy are at the age of 16-19 years with the 60,00% of indigenous ethnic group in 62,50%, 72,50% of rural origin, students occupying 50,00%, 30,00% perform household chores. The 42,50% are single mothers and 30,00% cohabiting, 27,50% are married. It was found that 80,00% of pregnant women have complications. 37,50% of them with urinary tract infection, 22,50% emergency cesarean sections were performed; 12,50% he presented rupture of membranes; 12,50%, preterm labor, anemia 7,50%. As neonatal jaundice complications was found 32,50%, low birth weight 20,00% and 15,00% suffocation, premature infant 12,50%, 12,50% risk of sepsis. The main risk factors of ignorance in 42,50%, followed by migration problems in the 40,00%, with 47,50% lack of dialogue between parents and children, did not have family support with 45,00% They became pregnant by sexual abuse 8,00%. Main factor influencing for complications is the lack of risks at 47,50%. It is concluded that the teen 16-19 years of indigenous ethnicity are most present complications, the leading cause is ignorance. The authoress realized educational activities in schools, workshops